(untitled) (Research, Society and Development, 2020)
Food deficiency and physical inactivity are factors that influence the quality and life expectancy of human beings, impairing their immunity to possible health problems, giving rise to contamination by SARS-CoV-2 viruses that mainly affect people with malabsorption of nutrients. The Covid-19 disease virus in contact with the mouth, eyes and nose where it binds like cells of the mucosa that creates new cells that multiply contaminating cells that cause symptoms that cause mild symptoms such as sore throat, cough and fever, reaching symptoms more serious that can be fatal due to the difficulty in breathing, affecting the health of the elderly and vulnerable people with respiratory problems. Why care methods should be avoided, starting with food as a form of care and avoiding vitamin D supplementation.